Transcriptomic and metabolomic profiling of Camellia oleifera seedling roots treated with different nitrogen forms - Zhou, J.; Liu, Y.; Chen, M.; Tan, X.; Yuan, J.
Nitrogen (N)is an essential nutrient for plant growth, but its availability is limited in the soil of subtropical ecosystems. Identifying the genes responsible for N utilization efficiency (NUE)in Camellia oleifera is important because of the excessive cost of N fertilization. To investigate this, we performed RNA-sequencing of C. oleifera roots to reveal the genome-wide gene expression in response to three synthetic forms of N, namely ammonium (NH?+?4), nitrate (NO- 3), and ammonium nitrate (NH4NO3), provided to three independent groups of plants. The expression of several ammonium and nitrate transporters increased slightly in the NO- 3-treated group and significant changes were observed in the NH?+?4- and NH4NO3-treated groups. The opposite expressions of some key N transport and assimilation genes under the different N treatments suggested that C. oleifera might have different N utilization pathways for the different N forma. Additionally, the genes involved in N transport and assimilation account for the different N uptake and for different concentrations of glutamate and glutamine in plants and the metabolomic data showed that the accumulation of both amino-acids was promoted by the NH?+?4 and NH4NO3 treatments but not by the NO- 3 treatment. These findings will help improve the NUE of C. oleifera and guide its agricultural production in the future.
Keywords: TEA OIL CAMELLIA; METABOLOME; TRANSCRIPTOME; NITROGEN FORMS; TRANSPORTERS